On peculiarities of native-metallic mineralization in the lavabreccia of the Lower-Vendian basalt formation of Volyn - Lukin, A. E.; Derevskaya, E. I.; Rudenko, K.V. (Reports of the National Academy of Sciences of Ukraine, 2014)
The abundant of dispersion native-metallic particles in lavabreccia, their geochemical diversity, and morphological peculiarities support the connection of these micro- and nanoinclusions (and caused by them primary geochemical anomalies) with gas explosions within ascending flows of super-deep earth fluids. These data confirm the conception that gas explosions are the main factor in the explosive volcanic breccias formation. This allows one to use mineralogical diversity as a gold ore guides.